Ultrafast electronic phase transition in La1/2Sr3/2MnO4 by coherent vibrational excitation: evidence for nonthermal melting of orbital order. - Tobey, R; Prabhakaran, D; Boothroyd, A; Cavalleri, A (2008)
An ultrafast electronic phase transition, associated with melting of orbital order, is driven in La1/2Sr3/2MnO4 by selectively exciting the Mn-O stretching mode with femtosecond pulses at 16 microm wavelength. The energy coupled into this vibration is less than 1% of that necessary to induce the transition thermally. Nonthermal melting of this electronic phase originates from coherent lattice displacements comparable to the static Jahn-Teller distortion.